Medical and Scientific Illustration in the United States (US) - Peres, Michael (Journal of visual communication in medicine, 2015)
The field of Medical and Scientific Illustration in the United States is large and constantly changing. In 1974, when the author began his studies, everything about the field was different. At the time, a student in the U.S. could go to a number of Universities (4 year) or Colleges (2 year) to study this subject. More than forty years later, only a few programs still offer similar programs of study. The Rochester Institute of Technology (RIT), where the author is a professor and Randolph Community College in North Carolina are all that remain from the more than ten that had operated. These two programs are very different from one another and there is not adequate space in this article to expand on these differences. Program details can be found online at: http://cias.rit.edu/schools/photographic-arts-sciences/undergraduate-biomedical-photographic-communications